EXPERIMENTAL INVESTIGATION OF EFFERVESCENT ATOMIZATION: PART I. COMPARISON OF FLAT-END AND STREAMLINED AERATOR BODY DESIGNS - Niland, Andrew; Santhosh R.; Marsh, Richard; Bowen, Philip (Begell House Inc., 2022)
This study of effervescent atomization, a two-phase gas-liquid spray generation technique that offers many advantages over conventional atomizers, shows the advantage of streamlined aerator design over flat-end aerator type with respect to formation of gas-void in the aerator wake in the interior of an inside-out type of effervescent atomizer. The experiments use high-speed shadowgraphy visualizations. It is observed that, in the conventional flat-end type of aerator design, the formation of gas-void is undesirable and leads to spray characterized by instabilities, causing fluctuating spray properties. The existence of gas-void also prevents the formation of bubbly flow inside the effervescent atomizer, which is actually preferred in these types of atomizers to enable stable spray generation and fine atomization. The formation and existence of gas-void is a result of aerator bluff body recirculation and gas phase buoyancy effects. Four different streamlined aerator designs with tips in the shape of circular arc, circular arc/conical hybrid, conical, and DARPA SUBOFF afterbody design (which is common in the conventional ship designs) are evaluated to determine the best among them with respect to mitigating the unwanted gas-void in the interior of an effervescent atomizer. These are evaluated by their ability to produce bubbly flow over comparatively large operating range and the ability to impart minimum wake (of aerator body) effect. It is concluded, upon careful experimental observations, that the DARPA SUBOFF afterbody design is the best among the streamlined aerator designs.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: bubbly flow; effervescent atomization; gas-void; internal-flow visualization; streamlined aerator body; wake effect; Atomization; Buoyancy; Flow visualization; Wakes; Circular arc; Effervescent atomizers